Value of serum ferritin estimation in sickle cell anaemia. Issue 4 (April 1978) - Hussain, M A; Davis, L R; Laulicht, M; Hoffbrand, A V
Abstract : In a group of 35 children with sickle cell anaemia serum ferritin concentration ranged from 70 to 2460 microgram/l (mean 367, median 180 microgram/l). This was significantly higher than the ferritin levels (range 8-101, mean 34, median 30 microgram/l) in a group of 63 normal control children of the same age group. 30 (86%) of the sickle cell children showed serum ferritin levels greater than 101 microgram/l, and 2 (6%) levels greater than 1000 microgram/l. 7 of the patients had not been transfused before this study. Their serum ferritin levels were all raised and showed a significant correlation with age but not with haemoglobin level. In the remainder of the patients the serum ferritin bore no significant correlation with age, haemoglobin level, or number of units of blood transfused. 2 children with HbSC disease had levels within the control range. Since patients with sickle cell anaemia have an increasing chance of long survival, we suggest that serial estimations of their iron status be made by means of serum ferritin assay in order to determine which patients are accumulating excessive iron.